Dynamic Mixed Lubrication Investigation of Water-Lubricated Bearing With Unbalanced Rotor During Start-Up. Issue 4 (25th June 2021) - Xiang, Guo; Wang, Cheng; Wang, Yijia; Han, Yanfeng; Wang, Jiaxu; Lv, Zhongliang
Abstract: The main purpose of this study is to investigate the dynamic mixed elastohydrodynamic lubrication (DMEHL) behavior of the water-lubricated bearing with unbalanced rotor during start-up. To achieve this, a DMEHL model that couples the rotor dynamic model considering the unbalanced load with the transient mixed lubrication model is established. The validity of the calculation procedure is verified by comparisons with published experimental and numerical results. Using numerical studies, the optimal accelerating mode for reducing the transient asperity contact during start-up is identified. Numerical results indicate that during start-up, the rotor dynamic characteristic and hydrodynamic force are more sensitive to the unbalanced load than the transient contact force, and the rotor imbalance eccentricity will affect the transient contact behaviors if the surface roughness is relatively large. In addition, the DMEHL responses are affected by the unbalanced load only when the accelerating time is small. Finally, the DMEHL responses during start-up using three different water-lubricated materials, namely, polymer, Thordon, and ceramic, are compared. It is found that DMEHL performance at the start-up stage highly depends on the elastic modulus and hardness of the water-lubricated material.